A discrete packing model of granular material confined in a vertical column. (6th April 2020) - Jiang, Qinghai; Wu, Kai; Sun, Yu; Xie, Xin; Yang, Zhengyu
In this paper, we analysed the transmission rules of interparticle forces between granular particles, based on which, we then proposed a discrete packing model to calculate the static pressure at the bottom of granular material confined in a vertical column. Our mechanical analysis and numerical simulation results indicate that the silo effect is caused by the frictional contacts between border particles and inner walls, the static pressure at the bottom depends on the external load initially, and then tends to a saturation pressure ( Pn ) in an exponential form. The saturation pressure is positive linear related to the container radius ( R ) with the same granular matter and stacking manner. The saturation pressure is directly proportional to the particle size ( ra ), and the increasing or decreasing characteristic depends on the frictional property of inner walls, the friction and stacking angle of grains. Finally, we compared the predictions of the aforementioned model with the experimental results from the literature, and we observed that good agreement is achieved.